Stability of extemporaneous rifampicin prepared with X-temp® oral suspension system - Salma Nadirah Md Salim; Mohd Danial Mohd Murshid; Amirah Mohd Gazzali (IIUM Press, International Islamic University Malaysia, 2021)
Introduction: Rifampicin is a first line antituberculosis drug that is commonly used in the treatment of tuberculosis, both in adults and paediatric patients. However, there is a lack of liquid formulation for rifampicin in the market due to the small market size and the physicochemical properties of the drug itself. An innovative new mix called X-Temp® oral suspension system (OSS) has been available in the market as a choice of vehicle for extemporaneous suspension. Aim: The aim of this study was to prepare rifampicin suspension in the X-Temp® OSS and evaluate its stability following storage at two temperatures - refrigerated (5 °C ± 3 °C) and in a stability chamber (30 °C ± 2 °C/RH 75% ± 5%). Materials and method: This study investigates the physicochemical and microbiological stability of rifampicin formulated in X-temp® OSS. The rifampicin suspension was prepared at 25mg/ml and kept in two types of amber-coloured storage bottles. The bottles were stored in an open and close storage system at 5 oC (refrigeration) and 30 °C/75% RH (non-refrigerated) and the stability of the product was evaluated at specified time intervals. Results: It was found that the content of rifampicin remained above 90% of the original concentration throughout the study as required by the standard references. Visual appearance, colour, odour and pH remained unchanged throughout the study period and the extemporaneous preparation was not susceptible to microbial contamination. Conclusion: Results from this stability study confirmed that the X-temp® OSS is a suitable vehicle for the preparation of extemporaneous rifampicin liquid formulation.